(untitled) (Research, Society and Development, 2023)
Leptospirosis in na emerging bacterial disease, considered the most widespread zoonosis in the world, sinse it has already been observed in more than 150 species of mammals, with carrier animals considered key in the disease transmission cycle. This Variety of hosts and the evasion capacity of the imune system guarantee the permanence and perpetuation of the agente, resulting in na importante problem for Animal and Public Health. Therefore, the objective of this study was to carry out a bibliographical survey gathering works referring to the main reservoir animals of Leptospirosis and to highlight public environmental and health policies that govern the prevention and treatment of the disease. The procedure used was the narrative bibliographic review, Where the works presented are dated between 2010 and 2023 and databases such as Google school, Scielo, Pubmed and Periódicos Capes were accessed in order to Search for indexed articles, using Keywords. It can be seen that Leptospirosis is a disease with varied etiology having a range of animal reservoirs that can infect humans. Treated as a neglected disease, Leptospirosis is a disease with a global incidence, with greater attention to tropical countries, including Brazil. In Brazil, it can be found in all regions, especially the South and Southeast, with the disease being epidemic in the rainy season. There are laws that draw attention to Leptospirosis, mainly for its prevention, however, the disease deserves to be treated with greater attention given its incidence throughout the country, with the need for greater investment in the Pharmaceutical industry and research.